IDENTIFIKASI BAKTERI PELARUT POSFAT PADA RIZOSFER UBI JALAR VARIETAS RANCING SELAMA FASE PERTUMBUHAN - Rizki Amelia Nasution (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
Cilembu Sweet Potato is one type of sweet potato that is typical in the West Java area precisely in the Cilembu village or Sumedang. Cilembu sweet potato has a typical characteristic that is taste like honey if it fermentation and then roasted. Rizospheric bacteria with the ability of phosphate solvents are one of the factors supporting growth in plants. The research aims to identify Rhizosphere bacteria in Cilembu sweet potato roots which have the ability as phosphate solvents at two locations during the growth phase. The study was conducted with qualitative by testing the biochemical characteristics and ability of phosphate solvents. The result of this research show that Rhizosphere bacteria with the ability of phosphate solvents at the location of Cilembu (LCI) and Jatinangor (LJA) are not significantly different. In LCI, 12 isolates were obtained and in LJA 7 isolates were obtained. So that it can be concluded that the diversity of rhizosphere bacteria can be influenced by the characteristics of the soil and the growth phase.Keywords: Cilembu yam, Rizosphere bacteria, phosphate solvent